2011
DOI: 10.1002/pts.987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimicrobial Starch Edible Coating on Shelf‐Life of Fresh Strawberries

Abstract: Strawberry is a very sensitive fruit and presents a short post‐harvest shelf‐life. Among the factors responsible for strawberries' quality loss are high metabolic activities and mold decay. To increase product shelf‐life, cassava starch–based edible coatings (3%), added or not with potassium sorbate (0.05%), were applied on minimally processed strawberries. Uncoated minimally processed strawberries were used as control samples. Physical and chemical properties, respiration rate and sensorial acceptance of unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 41 publications
6
29
0
5
Order By: Relevance
“…At time 0 the fruits treated with CS + P66% showed the highest levels, but there was a decrease over time, and from the 8th day this treatment showed the lowest anthocyanin level by the end of storage, showing that CS + P66% was ineffective in maintaining anthocyanin content in stored strawberry fruit. Despite the variation undergone during the storage, at the end of 16 days, the control fruit presented higher content compared to the coated fruit, a result similar to that reported by Garcia et al (2012), who, when using a cassava starch based coating (3%) on minimally processed strawberry, observed higher anthocyanin levels in uncoated fruits after 15 days. Similarly, Gol, Patel and Rao (2013) reported that strawberries coated with carboxymethyl cellulose and hydroxymethyl cellulose in combination with chitosan showed lower anthocyanin content than the uncoated fruit when stored for 12 days at 11 ºC.…”
Section: Resultssupporting
confidence: 87%
“…At time 0 the fruits treated with CS + P66% showed the highest levels, but there was a decrease over time, and from the 8th day this treatment showed the lowest anthocyanin level by the end of storage, showing that CS + P66% was ineffective in maintaining anthocyanin content in stored strawberry fruit. Despite the variation undergone during the storage, at the end of 16 days, the control fruit presented higher content compared to the coated fruit, a result similar to that reported by Garcia et al (2012), who, when using a cassava starch based coating (3%) on minimally processed strawberry, observed higher anthocyanin levels in uncoated fruits after 15 days. Similarly, Gol, Patel and Rao (2013) reported that strawberries coated with carboxymethyl cellulose and hydroxymethyl cellulose in combination with chitosan showed lower anthocyanin content than the uncoated fruit when stored for 12 days at 11 ºC.…”
Section: Resultssupporting
confidence: 87%
“…Fruit intrinsic factors, such as transpiration processes, temperature, among others point out an increase in sugar metabolism consumed by fruit respiration. Garcia et al (2012) also confirmed this process in fresh-cut strawberry. Nonetheless, soluble solids content tends to increase with fruit ripening through biochemical processes of polysaccharide degradation, which occurred in a study carried out by ŽNIDARČIČ et al (2010) in tomato cultivar Belle.…”
Section: Resultssupporting
confidence: 64%
“…Numerous trials have been aimed at the invention of an appropriate technology for KS-containing antimicrobial polymer materials. A great deal of research has been dedicated to developing active packages through the use of edible films and coatings (Basch et al 2013;Famá et al 2005;Flores et al 2007;Garcia et al 2012;Kristo et al 2008;Mehyar et al 2014;Ofman et al 2004;Floros 2001, 2003;Pérez et al 2014;Sayanjali et al 2011;Shen et al 2010;Valencia-Chamorro et al 2008). The application of these kinds of materials is one of the innovations of packaging technology aiming to improve the mechanical properties of the food, minimize respiration in fruits and vegetables, limit the movement of moisture and other gases, provide antimicrobial or antioxidant capabilities to the product, enhance the sensory properties, and extend the shelf life of the product.…”
Section: Introductionmentioning
confidence: 99%